Macroeconomic Determinants of Capital Flight: An Empirical Study in Malaysia - Liew, Siew-Ling; Shazali, Abu Mansor; Puah, Chin-Hong (Medwell Journals, 2016)
This study aimed to examine empirically the macroeconomic determinants of capital flight in Malaysia, namely the Foreign Direct Investment (FDI), external debt, stock market and political risk. To perform the empirical research, the Augmented Dickey-Fuller (ADF) and Phillips-Peron (PP) unit root tests as well as the Kwiatkowski-Phillips-Schmidt-Shin (KPSS) stationary test were conducted to examine the order of integration of the variables. Bounds test for cointegration and the Autoregressive-Distributed Lag (ARDL) approach were utilized to determine the factors affecting capital flight in Malaysia by employing the measure of World Bank (1985). Empirical results indicated that there is a long-run relationship among the variables under study. The findings denoted that political risk and financial crisis are positively related to capital flight in Malaysia, whereas FDI, external debt and stock market have negative impact on capital flight. In addition, the results also indicated that there is a short-run causal impact running from specific determinants towards capital flight. This study suggests that the government should implement appropriate economic policies to reduce capital flight in Malaysia. This is because the management of capital flight and macroeconomic policies has become increasingly important in an ever more integrated global economy.